Pineapple peel as an alternative substrate for production of bacterial nanocellulose - Lee, Adriana Connie (2022)
Bacterial nanocellulose (BNC) is a nano fibrillar polymer produced by nanocellulose producing bacteria such as Acetobacter xylinum. The diverse characteristics of BNC such as chemical purity, high mechanical strength, high flexibility, high absorbency, and the ability to create any shape or size and others that have attracted a lot of interest. The BNC’s broad usage in food technology, paper, and electronics as well as the architecture in use, is due to its vast number of benefits. However, using commercial glucose as a carbon source in a media such as Hestrin and Schramm (HS) medium in large-scale synthesis of BNC is expensive. As a result, most researchers are looking for alternative substrates from accessible wastes to reduce the cost of BNC production. Thus, this research is aimed to investigate the synthesis of BNC by an isolated bacterial strain using an agro-industrial waste which is the pineapple peel extract. Six bacterial strains namely F8, F5, M1, M6, H7 and H11 were screened and identified for potential BNC producer. The selected bacterial strain was identified as Bacillus cereus MMS1 using 16S rRNA nucleotide sequences. Then, the production of BNC was done by B. cereus MMS1 using pineapple peel extract, while A. xylinum ATCC2376 was acted as a control. The BNC production in this study was attained at 2% (w/v) glucose concentration, 12 days of incubation period and 150 rpm agitation speed which was 5.83 g/L by A. xylinum ATCC2376 in HS medium using commercial glucose as carbon source. Meanwhile, 4.42 g/L and 2 g/L of BNC were produced by B. cereus MMS1 after 12 days of incubation with an initial concentration of 2% (w/v) using commercial glucose and pineapple peel extract, respectively. The fermentation effects of BNC production concludes that the optimum condition to produce BNC by using pineapple peel extract as an alternative substrate is 2% (w/v) carbon source concentration, 12 days of incubation period and 150 rpm agitation. This study showed that agro-industrial wastes such as the pineapple peel may be used in place of costly substrates to produce BNC.